Perceptions and Predictors of Consumers’ Purchase Intentions for Store Brands: Evidence from Malaysia - Tih, Siohong; Kean, Heng Lee (Asian Journal of Business and Accounting, 2017)
This study examines consumers’ perceptions of retail store brands and identifies the predictors of purchase intentions for the store brands. To examine the proposed research model, two independent samples are drawn. The first sample consists of 120 responses collected via mall intercept at a famous hypermarket retail chain store, and the second sample consists of 120 responses also collected using the mall intercept method at a supermarket chain store in Klang Valley, Malaysia. Multiple regressions are used to test the hypotheses. There are mixed results in relation to the tested relationships. Perceived value for the money, perceived quality variance, perceived price and perceived risk have a significant impact on consumer purchase intention for the store brand in the hypermarket sample. However, analysis using the supermarket sample indicated that only perceived quality variance has a significant impact on consumer purchase intention for the store brand. Keywords: Consumer Perception, Purchase Intention, Store Brand JEL Classification: M31